Performance and Efficiency of an Autoclave Made from Local Materials in Winter and Summer in Iraq - Nada S. Saleh; Hazim H. Hussain; Ahmed Abdelhalim (Al-Mustansiriyah Journal of Science)
A solar-powered autoclave, made of a parabolic dish reflector that collects solar radiation at the focal point to heat a vessel, was established and tested. Thermal performance was tested and compared between months June and December 2022 through thermal energy efficiency equations and the total required thermal energy to evaporate water and the required thermal energy, where the highest values in June 2022 were 9%, 46 W, and 18 W, respectively at 9:00 am. Because solar radiation values are low, the energy required for heating is high and the lowest values were 0.2%, 1.9 W, and 0.5 W, respectively at 12:30 pm Because solar radiation values are high, the energy required for heating is less. While the highest values on December 2022 were 22%, 23 W, and 14 W, respectively, at 9:00 am, the lowest values were 0.6%, 1.16 W, and 6.6 W, respectively. At 12:00 pm, the values of December are considered higher for several reasons, including the values of solar radiation and the ambient temperature are lower than those of June, as well as the difference in the angle of incidence of solar radiation, so the thermal energy required for heating is higher. The effectiveness was tested against pseudomonas aeruginosa bacteria and samples of surgical kits made of stainless steel, where the highest values of steam temperatures for sterilization were recorded between 122 °C to 132 °C. Under a steam pressure of 1.3 to 1.9 bar between 11:00 am to 3:00 pm, one sterilization cycle took 30 minutes in June 2022, and for the month December 2022 the highest values of steam temperatures for sterilization were between 101 °C to 117 °C. Under steam pressure 0.7 to 1.03 bar between the hours 10:30 am to 12:30 pm, where the sterilization cycle was between 40 to 60 minutes, as a result of the decrease in solar radiation.